International Journal of Coal Science & Technology - Peng, Suping
The International Journal of Coal Science & Technology is a peer-reviewed Open Access journal focusing on key topics of coal scientific research and mining development. It will serve as an international forum for scientists to present their research findings, and to discuss new developments and challenging issues in the field.   The scope of coverage is broad, extending to such topics as:   Coal geology, geochemistry, geophysics, mineralogy and petrology – coal basin and coal seam formation and evolution; petrology of coal; organic matter-rich shales, including mineralogy, geochemistry, formation, transport and storage of gases in coal and shales; unconventional energy systems (e.g. oil shales, shale gas, and other carbon-based fuels); ore deposits of materials and rare metals in coal and coal-bearing strata; and groundwater management     Coal mining theory, technology and engineering – coal-measure rocks/ground behavior; mine construction; drift excavation; grouting; support technology; tunnels; mining disaster prevention; green mining; top coal caving; systematic mining technology for super-thick or thin seams; CBM exploration and management     Coal processing, utilization and conversion – coal chemistry; beneficiation; liquefaction; gasification; coal water slurry; coal power plant; combustion; coking; by and end products of coal utilization; clean coal technology; low carbon technology; CC(U)S; and IGCC     Coal mining environment and reclamation – Waste management and waste minimization practices; coal mine site closure, decommissioning and reclamation; adverse effects of toxic elements during coal utilization and mining; post-combustion pollution control; waste disposal; and mine water drainage     Other key topics relating to coal science and technology – mine survey; mine health and safety; CO2 mineralization and utilization etc.   .